A High-Security and Smart Interaction System Based on Hand Gesture Recognition for Internet of Things. (6th June 2018) - Xu, Jun; Zhang, Xiong; Zhou, Meng
Abstract : In this work, we propose a vision-based hand gesture recognition system to provide a high-security and smart node in the application layer of Internet of Things. The system can be installed in any terminal device with a monocular camera and interact with users by recognizing pointing gestures in the captured images. The interaction information is determined by a straight line from the user's eye to the tip of the index finger, which achieves real-time and authentic data communication. The system mainly contains two modules. The first module is an edge repair-based hand subpart segmentation algorithm which combines pictorial structures and edge information to extract hand regions from complex backgrounds. Second, the position which the user focuses on is located by an adaptive method of pointing gesture estimation, which adjusts the offsets between the target position and the calculated position due to lack of depth information.